Uterotonic agents for preventing postpartum haemorrhage: A network meta-analysis - Gallos, Ioannis D. (2018)
Background: Postpartum haemorrhage (PPH) is the leading cause of maternal mortality worldwide. Prophylactic uterotonic agents can prevent PPH, and are routinely recommended. The current World Health Organization (WHO) recommendation for preventing PPH is 10 IU (international units) of intramuscular or intravenous oxytocin. There are several uterotonic agents for preventing PPH but there is still uncertainty about which agent is most effective with the least side effects. This is an update of a Cochrane Review which was first published in April 2018 and was updated to incorporate results from a recent large WHO trial. Objectives: To identify the most effective uterotonic agent(s) to prevent PPH with the least side effects, and generate a ranking according to their effectiveness and side-effect profile. Search methods: We searched the Cochrane Pregnancy and Childbirth's Trials Register, ClinicalTrials.gov, the World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP) (24 May 2018), and reference lists of retrieved studies. Selection criteria: All randomised controlled trials or cluster-randomised trials comparing the effectiveness and side effects of uterotonic agents with other uterotonic agents, placebo or no treatment for preventing PPH were eligible for inclusion. Quasi-randomised trials were excluded. Randomised trials published only as abstracts were eligible if sufficient information could be retrieved. Data collection and analysis: At least three review authors independently assessed trials for inclusion and risk of bias, extracted data and checked them for accuracy. We estimated the relative effects and rankings for preventing PPH = 500 mL and PPH = 1000 mL as primary outcomes. Secondary outcomes included blood loss and related outcomes, morbidity outcomes, maternal well-being and satisfaction and side effects. Primary outcomes were also reported for pre-specified subgroups, stratifying by mode of birth, prior risk of PPH, healthcare setting, dosage, regimen and route of administration. We performed pairwise meta-analyses and network meta-analysis to determine the relative effects and rankings of all available agents. Main results: The network meta-analysis included 196 trials (135,559 women) involving seven uterotonic agents and placebo or no treatment, conducted across 53 countries (including high-, middle- and low-income countries). Most trials were performed in a hospital setting (187/196, 95.4%) with women undergoing a vaginal birth (71.5%, 140/196). Relative effects from the network meta-analysis suggested that all agents were effective for preventing PPH = 500 mL when compared with placebo or no treatment. The three highest ranked uterotonic agents for prevention of PPH = 500 mL were ergometrine plus oxytocin combination, misoprostol plus oxytocin combination and carbetocin. There is evidence that ergometrine plus oxytocin (RR 0.70, 95% CI 0.59 to 0.84, moderate certainty), carbetocin (RR 0.72, 95% CI 0.56 to 0.93, moderate certainty) and misoprostol plus oxytocin (RR 0.70, 95% CI 0.58 to 0.86, low certainty) may reduce PPH = 500 mL compared with oxytocin. Low-certainty evidence suggests that misoprostol, injectable prostaglandins, and ergometrine may make little or no difference to this outcome compared with oxytocin. All agents except ergometrine and injectable prostaglandins were effective for preventing PPH = 1000 mL when compared with placebo or no treatment. High-certainty evidence suggests that ergometrine plus oxytocin (RR 0.83, 95% CI 0.66 to 1.03) and misoprostol plus oxytocin (RR 0.88, 95% CI 0.70 to 1.11) make little or no difference in the outcome of PPH = 1000 mL compared with oxytocin. Low-certainty evidence suggests that ergometrine may make little or no difference to this outcome compared with oxytocin meanwhile the evidence on carbetocin was of very low certainty. High-certainty evidence suggests that misoprostol is less effective in preventing PPH = 1000 mL when compared with oxytocin (RR 1.19, 95% CI 1.01 to 1.42). Despite the comparable relative treatment effects between all uterotonics (except misoprostol) and oxytocin, ergometrine plus oxytocin, misoprostol plus oxytocin combinations and carbetocin were the highest ranked agents for PPH = 1000 mL. Misoprostol plus oxytocin reduces the use of additional uterotonics (RR 0.56, 95% CI 0.42 to 0.73, high certainty) and probably also reduces the risk of blood transfusion (RR 0.51, 95% CI 0.37 to 0.70, moderate certainty) when compared with oxytocin. Carbetocin, injectable prostaglandins and ergometrine plus oxytocin may also reduce the use of additional uterotonics but the certainty of the evidence is low. No meaningful differences could be detected between all agents for maternal deaths or severe morbidity as these outcomes were rare in the included randomised trials where they were reported. The two combination regimens were associated with important side effects. When compared with oxytocin, misoprostol plus oxytocin combination increases the likelihood of vomiting (RR 2.11, 95% CI 1.39 to 3.18, high certainty) and fever (RR 3.14, 95% CI 2.20 to 4.49, moderate certainty). Ergometrine plus oxytocin increases the likelihood of vomiting (RR 2.93, 95% CI 2.08 to 4.13, moderate certainty) and may make little or no difference to the risk of hypertension, however absolute effects varied considerably and the certainty of the evidence was low for this outcome. Subgroup analyses did not reveal important subgroup differences by mode of birth (caesarean versus vaginal birth), setting (hospital versus community), risk of PPH (high versus low risk for PPH), dose of misoprostol (= 600 mcg versus < 600 mcg) and regimen of oxytocin (bolus versus bolus plus infusion versus infusion only). Authors' conclusions: All agents were generally effective for preventing PPH when compared with placebo or no treatment. Ergometrine plus oxytocin combination, carbetocin, and misoprostol plus oxytocin combination may have some additional desirable effects compared with the current standard oxytocin. The two combination regimens, however, are associated with significant side effects. Carbetocin may be more effective than oxytocin for some outcomes without an increase in side effects.